1972
DOI: 10.1021/es60066a006
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-nitrogen removal by breakpoint chlorination

Abstract: The normal composition of the effluent samples at Abbott Laboratories is within the maximum tolerated impurity levels as listed in the Illinois State Standards (1968). These tolerances are partially summarized in Table I and do not interfere in the assay. Wiersma (1970) employed 2,3-diaminonaphthalene as a fluorometric reagent for nitrite ion and in addition performed Table I. Illinois Effluent Standards Constituent" Standard Ammonia nitrogen 2.5 ppm Arsenic 1.0 ppm BOD 40 mg/1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
0
3

Year Published

1974
1974
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(135 citation statements)
references
References 5 publications
7
125
0
3
Order By: Relevance
“…The HOCl further reacts with NH 3 and produces N 2 [10]. It has been also reported that Ti/TiO 2 -RuO 2 anode can efficiently remove NH 3 with the appropriate amount of Cl -concentration in the electrolyte [11].…”
Section: Nitrate Removal Using Electrochemically Produced Hoclmentioning
confidence: 98%
“…The HOCl further reacts with NH 3 and produces N 2 [10]. It has been also reported that Ti/TiO 2 -RuO 2 anode can efficiently remove NH 3 with the appropriate amount of Cl -concentration in the electrolyte [11].…”
Section: Nitrate Removal Using Electrochemically Produced Hoclmentioning
confidence: 98%
“…Approximately 14 percent of the oxidized ammonium and urea in the buffered groundwater samples treated with hypochlorite formed nitrate, while in the unbuffered samples (pH Ͻ 4) ~7 percent of the oxidized ammonium and urea formed nitrate. Pressley et al (1972) indicated that nitrate production was pH-dependent and that lowering the pH to 6 reduced nitrate formation to approximately 1 percent.…”
Section: Bench-scale Experimentsmentioning
confidence: 99%
“…When the chlorine dosage exceeds approximately ten times the concentration of ammonia nitrogen by weight, a process known as the breakpoint reaction occurs (76). By a series of reactions most of the ammonia nitrogen is oxidized to nitrous oxide or nitrogen gas.…”
Section: Chlorine Species In Solutionmentioning
confidence: 99%